1989
DOI: 10.1111/j.1745-3992.1989.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Inside High School Grading Practices: Building a Research Agenda

Abstract: Do teachers actually follow the grading practices recommended by researchers and textbook authors? where are the discrepancies? What are possible explanations for such discrepancies? What is an agenda for further research on actual classroom grading practices of teachers?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
2
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 8 publications
(4 reference statements)
7
69
2
3
Order By: Relevance
“…Compared to the other areas of the educational assessment process, the participating teachers reported a lower practice related to the analysis of the assessment results and student involvement in the assessment process. Also, they reported using non-achievement grading factors when assigning grades for students, which in turn, do not align with those recommended by educational assessment experts which state that non-achievement factors such as effort, ability, interest, and motivation should not be incorporated into academic grades because they are complex to be operationally defined and measured (Stiggins, Frisbie, & Griswold, 1989). The results of the study indicated that teaching load and educational assessment training may play a critical role in teachers' attitudes, competence, knowledge, and practices in educational assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the other areas of the educational assessment process, the participating teachers reported a lower practice related to the analysis of the assessment results and student involvement in the assessment process. Also, they reported using non-achievement grading factors when assigning grades for students, which in turn, do not align with those recommended by educational assessment experts which state that non-achievement factors such as effort, ability, interest, and motivation should not be incorporated into academic grades because they are complex to be operationally defined and measured (Stiggins, Frisbie, & Griswold, 1989). The results of the study indicated that teaching load and educational assessment training may play a critical role in teachers' attitudes, competence, knowledge, and practices in educational assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers struggle to weigh non-achievement factors, yet valuing students' effort and dispositions is understandable since those characteristics contribute to students' comprehensive academic success (McMillan, 2008). Teachers regularly take into account student cognitive capacity, motivation, and work habits to adjust their expectations for individual students, which are sometimes recognized explicitly, such as by including non-achievement factors on a rubric, but are most often considered implicitly (Bowers, 2011;Lekholm & Cliffordson, 2008;Stiggins, Frisbie, & Griswold, 1989). Brookhart (1993) found that teachers give low-achieving students inflated grades for trying hard, even if their performance was below what they were capable of, yet teachers graded average and above-average students based more on their actual achievement.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Grades should be based on achievement factors only (Cizek, & Fitzgerald, 1996;Stiggins, Frisbie & Griswold, 1989). Brookhart (1997) found that teachers make value judgments when assigning grades.…”
Section: Grading As Feedbackmentioning
confidence: 99%
“…Since grade-based decisions may have lasting academic and social consequences (Messick, 1989;Popham, 2001), teachers should weigh assessment elements according to instructional emphasis (Airasian, 1991;Stiggins, Frisbie & Griswold, 1989). For example, if the main point of a writing lesson was proper nouns, then scoring should focus on proper nouns.…”
Section: Grading As Feedbackmentioning
confidence: 99%
See 1 more Smart Citation